(3GOGQI GdLhOI GdTGedI (B/s - (3GdYRGhj, eMeOYHO GdhgGHs ((3YeGf(B: s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B, s, 2005)
(3eaghe GdLhOI h eONd aj GOGQI GdLhOI GdTGedI h cPG eHGOF h eJWdHGJ GOGQI GdLhOI GdTGedI GVGaI Gdi GOhGJ GOGQI GdLhOI GdTGedI (B-(3eNWWGJ GdQbGHI h GNjQG GOhGJ GOGQI GdLhOI GdTGedI NQGFW GdeQGbHI(B.s
(3eQGLY U(B.151s
Keywords: (3GOGQI GdGfJGLs; (3GOGQI GdLhOI GdTGedIs